Influence of Agronomic Managements on Growth and Yield of Boro Rice (Bangladesh Agronomy Journal, 2023)
The study was carried out at Sher-e-Bangla Agricultural University, Dhaka from December 2018 to April 2019, to find out the agronomic practices on the growth and yield of Boro The trial was conducted with two rice varieties namely V1 (BRRI dhan84) and V2 (BRRI hybriddhan5), and 5 different agronomic practices such as M0 (no management), where variety in maim-plot and management practices in sub-plot. The results showed significant variations in weed severity, and l yield of Boro rice. Specific observations included plants reaching heights of 24.81 cm, 51.56 cm, 86.71 cm, and 119.21 cm at 20, 45, 70 days after transplanting (DAT), and at harvest, respectively. V2 exhibited a higher grain yield (5.36 t ha−1) but a reduced straw yield (4.97 t ha−1) compared to V1. Generally, regardless of the agronomic practices, BRRI dhan84 exhibited greater plant height, except under the 'no management' practice. The grain yield (6.70 t ha−1) was obtained with M6, and the maximum straw yield (6.55 t ha−1) to M4. The interaction effects showed that highest grain yield (7.35 t ha−1) from V2M6, while with V1M0.The most significant yield reduction for BRRI dhan84 was 84% with no management and 80% with no fertilizer, while BRRI hybriddhan5 showed a 71% reduction under similar conditions.Bangladesh Agron. J. 2023, 26(1): 104-111